Self-Hypnosis for Intrapartum Pain Management in Pregnant Nulliparous Women: A Randomized-Controlled Trial of Clinical Effectiveness. Issue 2 (June 2016) - Downe, S.; Finlayson, K.; Melvin, C.; Spiby, H.; Ali, S.; Diggle, P.; Gyte, G.; Hinder, S.; Miller, V.; Slade, P.; Trepel, D.; Weeks, A.; et al.
Abstract : ( BJOG. 2015; 122:1226–1234) There has been a rising demand from the parturient population for alternative forms of labor pain relief beyond epidural analgesia. One of these alternatives, hypnosis, might be able to reduce the use of epidural analgesia for labor and potentially decrease the need for interventions (eg, instrumental birth, neonatal antibiotic administration related to maternal fever). Subsequently, in this multicenter, nonblinded, randomized-controlled trial, undertaken in the United Kingdom, the authors established a self-hypnosis group program for nulliparous women in their third trimester of pregnancy (27 to 32 wk gestation) and examined the program's effect on epidural use during labor.